1989
DOI: 10.1111/j.1476-5381.1989.tb12646.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neurotransmission in the guinea‐pig vas deferens by capsaicin: involvement of calcitonin gene‐related peptide and substance P

Abstract: 1 The effects of capsaicin, calcitonin gene-related peptide and substance P were studied via three parameters in the guinea-pig vas deferens: the overflow of ATP and of tritiated noradrenaline, the mechanical responses to field stimulation and the mechanical responses to exogenous noradrenaline and a4,-methylene ATP. 2 At 2 Hz, capsaicin inhibited the stimulus-evoked release of ATP, whereas it was without effect on the release of noradrenaline. At 20 Hz capsaicin did not affect the release of either of the cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The site of action of tachykinins in the guinea-pig vas deferens is unclear. A postjunctional site on the smooth muscle has been suggested by Ellis & Burnstock (1989) longitudinal muscle of the guinea-pig vas deferens, and post-junctional neurokinin (NK1) receptors on the innner longitudinal smooth muscle has been proposed from autoradiographic studies (Mussop et al, 1989). It therefore seems unresolved whether both pre-(on sensory or sympathetic) and post-junctional receptors are functionally involved in the potentiation of twitch responses by tachykinins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The site of action of tachykinins in the guinea-pig vas deferens is unclear. A postjunctional site on the smooth muscle has been suggested by Ellis & Burnstock (1989) longitudinal muscle of the guinea-pig vas deferens, and post-junctional neurokinin (NK1) receptors on the innner longitudinal smooth muscle has been proposed from autoradiographic studies (Mussop et al, 1989). It therefore seems unresolved whether both pre-(on sensory or sympathetic) and post-junctional receptors are functionally involved in the potentiation of twitch responses by tachykinins.…”
Section: Discussionmentioning
confidence: 99%
“…However, since its original classification as an SP-P (= NK1) (Watson et al, 1983), this preparation has been little studied in terms of neurokinin receptor subtypes or involvement of other mediators in responses to tachykinins. Pharmacological investigation of the site of action of tachykinins (Ellis & Burnstock, 1989) and the autoradiographic localisation of neurokinin receptors (Mussop et al, 1989) have, however, recently been reported. The rat vas deferens in contrast has been used extensively to study sympathetic neuromodulation, though here tachykinin action is mediated through interaction with NK2 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…When 100 pulses were applied, stimulated-ATP increased by 14.23 and 28 times above spontaneous levels (groups C and D). In the guinea-pig vas deferens, Ellis & Burnstock (1989) reported levels of ATP following stimulation of 1.95 ± 1.17 (n = 6) times above spontaneous levels at 2 Hz and 6.30 ± 1.11 (n = 6) times at 20 Hz, even so, the number of pulses used (240 pulses) was much higher. Kirkpatrick & Burnstock (1987) reported at 16 Hz a 50 fold increase of ATP efflux above spontaneous levels of release.…”
Section: The Effects Of Number Ofpulses On Stimulated-a Tp Overflowmentioning
confidence: 99%
“…The concentration of capsaicin that maximally activates non-specific cation channels in rat sensory neurones is >1 AM (Bevan & Szolcsanyi, 1990), and this concentration accords with that utilized for the neuropeptide depletion in isolated tissues (e.g. Saito et al, 1987;Ellis & Burnstock, 1989). Saito et al (1987) reported that capsaicin reversibly inhibited part of the neurogenic contraction at 0.1 JM, but the depletion of the neurotransmitter responsible for this inhibition (presumably, calcitonin-gene-related peptide) required 1 to 10 AM of capsaicin in smooth muscle of rat vas deferens.…”
Section: Discussionmentioning
confidence: 84%
“…Capsaicin has also been shown to block neurotransmission not mediated by adrenoceptors or acetylcholine receptors in various tissues. This block of 'non-adrenergic non-cholinergic' transmission is considered to be due to neuronal excitation and stTbsequent depletion of neuropeptides such as substance P (Szolcsanyi & Bartho, 1978;Ellis & Burnstock, 1989) or calcitonin gene-related peptide (CGRP; Franco-Cereceda & Lundberg, 1985;Saito et al, 1987), which exist, presumably, in sensory neurones.…”
Section: Introductionmentioning
confidence: 99%